The feasibility and acceptability of a dementia care training program for registered dietitian nutritionists. Issue 2 (3rd April 2023) - Douglas, Joy W.; Ferguson, Christine; Nolan, Beth
ABSTRACT: There is a need for more Registered Dietitian Nutritionists (RDNs) trained to provide nutritional care to older adults with dementia who experience mealtime difficulties. The purpose of this single-arm, pre/post pilot study was to adapt a generalized dementia care curriculum to the learning needs of RDNs who work with individuals with dementia and to determine the feasibility and acceptability of the adapted program. Using an existing evidence-based dementia care curriculum, the research team identified learning objectives and content pertinent to the scope of RDNs. The adapted program was piloted with RDNs who work with older adults with dementia. Twenty-five RDNs registered for the training while 80% (20) attended the training and completed the post-training survey. All participants agreed that the module met the learning needs of RDNs who work with older adults with dementia, the two-hour workshop was a good use of their time, and the experience and skills gained would be useful in their work as an RDN. Implementation costs totaled 1, 310. Based on the post-training feedback, the adapted program was deemed feasible and acceptable by RDN participants, who also expressed interest in using the module to train other caregivers on providing mealtime assistance to older adults with dementia.